Nucleotide and amino acid sequences of human intestinal alkaline phosphatase: close homology to placental alkaline phosphatase. - Henthorn, P S (1987)
A cDNA clone for human adult intestinal alkaline phosphatase (ALP) [orthophosphoric-monoester phosphohydrolase (alkaline optimum); EC 3.1.3.1] was isolated from a lambda gt11 expression library. The cDNA insert of this clone is 2513 base pairs in length and contains an open reading frame that encodes a 528-amino acid polypeptide. This deduced polypeptide contains the first 40 amino acids of human intestinal ALP, as determined by direct protein sequencing. Intestinal ALP shows 86.5% amino acid identity to placental (type 1) ALP and 56.6% amino acid identity to liver/bone/kidney ALP. In the 3'-untranslated regions, intestinal and placental ALP cDNAs are 73.5% identical (excluding gaps). The evolution of this multigene enzyme family is discussed.